Fullmetal alchemist. 20 - Arakawa, Hiromu, 1973- (VIZ Media, 2009)
"In an alchemical ritual gone wrong, Edward Elric lost his arm and his leg, and his brother Alphonse became nothing but a soul in a suit of armor. Equipped with mechanical 'auto-mail' limbs, Edward becomes a state alchemist, seeking the one thing that can restore his and his brother's bodies...the legendary Philosopher's Stone. Betrayal and double-crossing are the order of the day. Greed, Pride and Envy prove to be formidable enemies, but one homunculus seems to be having pangs of--could it be?--conscience. Ominous news spreads quickly about a mysterious portal. Will this gateway help the Elric brothers regain their natural bodies? And will the gigantic underground transmutation circle be completed, leading to a major regime change? Plus, a moving reunion between Al and someone from his past!"--p. [4] of cover.